The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1809-4430-eng.agric.v38n1p149-157/2018
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Phosphorus Losses by Water Erosion

Abstract: Phosphorus losses in runoff water and eroded sediment may increase the risk of eutrophication. Erosion prediction models can be used to assess and quantify nutrient losses and transport in different soil management scenarios. This study aimed to assess the performance of models to estimate the losses of available phosphorus in eroded sediments and assess their spatial variability pattern. The experiment was installed on a eutrophic Red Ultisol located in Tabapuã, northwestern São Paulo State, São Domingos Stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Our experiment covers a 3‐yr period following a one‐time application of manure compost. The lack of measurable increases in Hedley TP at the 10‐to‐30‐cm depth at Blue Creek could be linked to a combination of (a) surface loss of compost‐derived P due to water erosion at the Blue Creek site, which is located on a slight slope while Snowville is nearly level (Farias et al., 2018); (b) leaching; and/or (c) faster cycling of compost derived P due to higher available moisture at the 10‐to‐30‐cm depth.…”
Section: Resultsmentioning
confidence: 99%
“…Our experiment covers a 3‐yr period following a one‐time application of manure compost. The lack of measurable increases in Hedley TP at the 10‐to‐30‐cm depth at Blue Creek could be linked to a combination of (a) surface loss of compost‐derived P due to water erosion at the Blue Creek site, which is located on a slight slope while Snowville is nearly level (Farias et al., 2018); (b) leaching; and/or (c) faster cycling of compost derived P due to higher available moisture at the 10‐to‐30‐cm depth.…”
Section: Resultsmentioning
confidence: 99%
“…Szara (2019) reported that liming applied in combination with mineral fertilisers reduces sandy soil sorption capacity leading to higher soil profile phosphorus mobility, causing phosphorus release from the soil. Farias et al (2018) found that the highest losses of phosphorus occur on slopes with concave land forms, reaching values higher than 0.02 mg l -1 , which is a critical value for eutrophication.…”
Section: Soil Categorisation From the Point Of View Of Water Source Pmentioning
confidence: 96%
“…The model of P loss as a function of the dry mass of straw and the green cover showed similar behavior as for K: P loss increased with increasing dry mass of the straw and with decreasing green cover. Modeling P losses is relevant for assessing soil use and management, as P losses in runoff water can increase the risk of eutrophication (Farias et al 2018;Leite et al 2018;Wang et al 2018). Modeling nutrient losses in an Oxisol Bragantia, Campinas, 83, e20230191, 2024 Bertol et al (2003) investigated nutrient losses caused by water erosion and found that P concentrations within the runoff were consistently low across all treatments and rainfall sessions applied; a phenomenon potentially attributed to the scanty presence of this element in the soil and its strong colloidal adsorption.…”
Section: P Lossmentioning
confidence: 99%